2017
DOI: 10.1111/ppa.12768
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of triticale accessions for resistance to wheat bacterial leaf streak caused by Xanthomonas translucens pv. undulosa

Abstract: The bacterium Xanthomonas translucens pv. undulosa (Xtu) causes bacterial leaf streak (BLS) on wheat and other small grains. Several triticale accessions were reported to possess high levels of resistance to wheat Xtu strains. In this study, a worldwide collection of triticale accessions as well as the major North Dakota hard red spring and durum wheat cultivars were evaluated for reaction to two local Xtu strains. All wheat cultivars showed a susceptible reaction but a wide range of reactions was observed amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Virulence differences were also observed among strains within a pathovar (Cunfer and Scolari, ; Milus and Chalkly, ; Adhikari et al , ; Sapkota et al , ). Using pathogenicity tests on several wheat genotypes, Adhikari et al () found that X .…”
Section: Virulence and Pathogenicity Of X Translucensmentioning
confidence: 99%
See 3 more Smart Citations
“…Virulence differences were also observed among strains within a pathovar (Cunfer and Scolari, ; Milus and Chalkly, ; Adhikari et al , ; Sapkota et al , ). Using pathogenicity tests on several wheat genotypes, Adhikari et al () found that X .…”
Section: Virulence and Pathogenicity Of X Translucensmentioning
confidence: 99%
“…undulosa (Bragard et al , ; Giblot‐Ducray et al , ; Curland et al , ). Using a few strains isolated from wheat and barley, we showed that wheat strains ( undulosa ) were capable of causing lesions and water‐soaking symptoms on wheat, barley, and triticale (× Triticosecale ), while barley strains ( translucens ) were only able to cause lesions and water‐soaking symptom on barley (Sapkota et al , ; Figure ). However, Curland et al () reported that most X. translucens pv.…”
Section: Classification Nomenclature and Identification Of X Transmentioning
confidence: 99%
See 2 more Smart Citations
“…There is increasing interest in developing treatment options to combat BLS, including efforts to develop resistant germplasm in wheat (Sapkota et al 2018), but currently no major resistance is available for growers. There are no available chemical treatments, and antibiotics can quickly drive the development of resistance when applied in the field (Sundin and Wang 2018).…”
Section: Introductionmentioning
confidence: 99%